Applicability of internal preparations for viper venom (polon visa) in treating dengue hemorrhagic fever - WTN, Alwis; IGPR, Kulanatha (Indian Journal of Integrative Medicine, 2024)
Dengue is a worldwide major public health problem. Severe Dengue Fever causes Dengue Hemorrhagic Fever that can be correlated with Raktaṣtivi Sannipātaja Jvara. Ayurveda explained disease causes for a new disease (Nidānārthakara Roga), it said that hemorrhagic manifestations (Raktapitta) may be resulted from a fever (Jvara) in high temperature. Data has been obtained from main Ayurveda texts Caraka, Suśruta, Aṣṭāṃga Saṃgraha, Mādhava Nidāna, Bhāva Prakaśa, and Talpatē Piliyam, the Sri lankan traditional text book and from the scientific web journals. Recipes found for Polon Viṣa in Talpatē Piliyam. Data of pharmacodynamics were analyzed in percentage. Three dosage forms found from the Talpatē Piliyam. In the collected 146 formulae for Polon Viṣa; 91 fresh juice extracts (Yuṣa), 51 gruel (Kenda) and 4 decoctions (Kaṣāya). Most frequently used ingredients of all formulae had four pharmacodynamic effects i.e; Kaṣāya Rasa, Laghu Guṇa and Kaṭu Vipāka. Śīta Vīrya. Collectively they have the counteracting effects for hemorrhagic condition in Dengue Hemorrhagic Fever. Antipyretic actions of the ingredients, Pacify Rakta and Pitta disorders, Anti hemorrhagic, and hepatoprotective were main actions of the ingredients. The aforementioned facts lead to the conclusion that the pharmacodynamics and specific actions of these ingredients aid in halting the pathogenesis (Samprāpti Vighaṭana) of Dengue Hemorrhagic Fever. Notably, the ingredients Bo (Ficus religiosa), Karalhaba (Achyranthes aspera), Iguru (Zingiber officinale), Madurutala (Ocimum sanctum), Heerassa (Cissus quadrangularis), and Rasakinda (Tinospora cordifolia) are highlighted as having potential for oral preparation to treat DF and DHF based on their pharmacodynamic profiles.